The effect of formative test, individual assignment and group assignment on students' achievement in junior secondary school mathematics (2010)
The study investigated the extent to which formative test, individual assignment and group assignment determined students' achievement in mathematics. Four schools in Ijebu- North of Ogun state were purposively chosen and an intact class in JSS 2 was used for each group for the treatments with a fourth group as control. Pre-test was conducted for the four groups before the commencement of the teaching. Three groups were taught using three different strategies: formative test on the first group, individual assignment on the second group and focus on group assignment on the third group while the fourth was taught using conventional method of instruction. A post test was administered on the four groups. The results (pre-test and post- test) were subjected to analysis of convariance. It was revealed that formative test, individual assignment and group assignment significantly affected achievement in mathematics. The adjusted means showed that formative test has the highest mean of 28.44 followed by individual assignment with adjusted mean of 25.06; group assignment recorded an adjusted mean of 23.48 and control haad the least adjusted mean of 20.62. It was recommended among other things that teachers should regularly give a take home assignment in mathematics to students which should be promptly marked and recorded.